Usulan Penerapan Metode Six Sigma dengan Pendekatan DMAIC pada Pengendalian Kualitas Produk Air Anion Exchange No.2 Demin Plant di PT. XYZ - Azizah, Andi Muna; Iskandar, Raden Andang; Parji, Parji (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Quality control is a crucial factor that plays a major role in ensuring company operations run effectively and efficiently. This study aims to determine what factors cause defects in products that can affect water quality as well as to determine the sigma level and defect rate of Anion Exchange No.2 water products in three months. In data processing using the Six Sigma method with five stages known as DMAIC (define, measure, analyze, improve, and control). The use of the DMAIC stage aims to improve product quality control and reduce costs incurred due to defective products. The most influential factor in the production of Anion Exchange No.2 water is the material factor. From this research, it is known that the average DPMO value is 15980,38 and sigma value is 3,74 which is the achievement of the average sigma level of the Indonesia industry with a level value of 3 sigma.